PERCEPTION OF ACCOUNTING ORGANISATIONS NEEDS AND THE ROLE OF HIGHER EDUCATION INSTITUTIONS - Leite, Sónia Ruão (Advances in Social Sciences Research Journal, 2019)
As Community Based Research (CBR) gains currency as a ‘research strategy of choice’ for the community sector (and increasingly establishes itself as a credible research approach also in the academic sector) we believe there is a need to revisit what have become the conventions of CBR and consider how these are enacted in practice. We could verify that there are several Higher Education Institutions (HEI’s) with offices of support services to the community or with this type of goal in their research projects, a demand which is also demonstrated by the organisation that evaluates the HEI’s in Portugal. Mainly, the type of problems studied by the community support centres in universities, are related with health, disabilities, and social exclusion. The current investigation is innovative because it was performed in order to identify in what way the accounting organisations need the help of HEI’s to provide independent participatory research support in response to concerns experienced by these organisations. Through a questionnaire composed of open and closed questions it was our intention to obtain information regarding the perspective of accounting professionals considering the needs and gaps that they feel in their professional practice and how the HEI’s can contribute to help bridge these gaps.